Social Needs and Intention to Stay by Generation-Y Employees in the Banking Sector in Malaysia: the Mediating Role of Perceived Organizational Support - Zabedah Othman; Jugindar Singh Kartar Sing; Raemah Abdullah Hashim (2019)
This study examined the impact of social needs of Generation Y employees towards their intention to stay longer in organizations. The mediating role of perceived organizational support was also examined. In this quantitative research, data was collected using a survey method. The study population were Generation Y employees in the banking sector in Malaysia. Random sampling was used to collect data from 470 respondents. Self-administered questionnaires were delivered by hand. Structural equation modelling was used to test the relationships. The findings revealed that Gen Y employees’ social needs were positively related to their intention to stay. It was found that perceived organizational support mediated the relationship between the two constructs. The findings presented new insights into how Gen Y employees social needs can contribute to improving their intention to stay in the banking sector. Given the paucity of research in the context of the role of social needs and perceived organizational support, this study provides an understanding to organizations on the influence of social needs and perceived organizational support in improving retention of Gen-Y employees. (Abstract by authors)